The world impact of boron doped diamond electrodes and low-cost strategies for novel production systems for sustainable wastewater treatment - Oliveira, Kaíque S.G.C.; dos Santos, Elisama Vieira [UNESP]; Loor-Urgilés, Luis D.; Shabanloo, Amir; Martínez-Huitle, Carlos A. [UNESP] (Elsevier, 2025)
Conductive diamond films appeared as promising materials with exceptional electrochemical properties that allowed significant advances in scientific and engineering domains. Therefore, in this opinion, we have explored the world's impact of boron doped diamond electrodes regarding its use in wastewater and disinfection from the point of view of the published scientific communications, preparation methodologies and the commercialization of these materials by several companies in different countries. A brief discussion about the scientific centers and institutes that have dedicated efforts to investigate diamond electrochemistry and its applications, has been included. More specifically, an opinion about the improvements in the fabrication of novel BDD electrodes and the design and construction of small electrochemical devices with different BDD materials. Trends on electrochemical technologies, using home-built and commercial BDD electrodes in environmental applications, have been also explored. The most important low-cost strategies for novel production systems for sustainable wastewater treatment and disinfection have been summarized and described. Finally, some examples of the types and devices of use of BDD electrodes are presented.
Keywords: BDD systems; Boron doped diamond; Disinfection; Synthesis protocols; Water treatment